Overexpression of ß-Arrestin1 in the Rostral Ventrolateral Medulla Downregulates Angiotensin Receptor and Lowers Blood Pressure in Hypertension - Sun, Jia-Cen; Liu, Bing; Zhang, Ru-Wen; Jiao, Pei-Lei; Tan, Xing; Wang, Yang-Kai; Wang, Wei-Zhong (Frontiers in Physiology, 2018)
Background: Hypertension is characterized by sympathetic overactivity, which is associated with an enhancement in angiotensin receptor type I (AT1R) in the rostral ventrolateral medulla (RVLM). β-arrestin1, a canonical scaffold protein, has been suggested to show a negative effect on G protein-coupled receptors via its internalization and desensitization and/or the biased signaling pathway. The major objectives of the present study were to observe the effect of β-arrestin1 overexpression in the RVLM on cardiovascular regulation in spontaneously hypertensive rats (SHR), and further determine the effect of β-arrestin1 on AT1R expression in the RVLM. Methods: The animal model of β-arrestin1 overexpression was induced by bilateral injection of adeno-associated virus containing Arrb1 gene (AAV-Arrb1) into the RVLM of WKY and SHR. Results: β-arrestin1 was expressed on the pre-sympathetic neurons in the RVLM, and its expression in the RVLM was significantly (P<0.05) downregulated by an average of 64 % in SHR than WKY. Overexpression of β-arrestin1 in SHR significantly decreased baseline levels of blood pressure and renal sympathetic nerve activity, and attenuated cardiovascular effects induced by RVLM injection of angiotensin II (100 pmol). Furthermore, β-arrestin1 overexpression in the RVLM significantly reduced the expression of AT1R by 65% and NF-κB p65 phosphorylation by 66% in SHR. It was confirmed that β-arrestin1 overexpression in the RVLM led to an enhancement of interaction between β-arrestin1 and IκB-α. Conclusion: Overexpression of β-arrestin1 in the RVLM reduces BP and sympathetic outflow in hypertension, which may be associated with NFκB-mediated AT1R downregulation.